Jawabanmu

Jawaban paling cerdas!
2014-04-24T20:16:35+07:00
F(x) = px + q
f(-1) = -5
f(4) = 5
f(-6) = ?

fx = px + q
f(-1) = -1x + q = -5
f(4)  =  4x + q = 5
Kurangkan, q dengan q coret karna sama
-5x  = -10
x     = 2

Masukkan ke persamaan 2 ( f(4) = 4x + q = 5 )
masukkan x nya : 4(2) + q = 5
                           8 + q = 5
                           q       = 5 - 8
                           q       = -3
f(x) = px + q
f(-6) = -6(2) + (-3)
       = -12  + (-3)
       = -15
                          
1 5 1
2014-04-24T23:32:10+07:00
F(×) = P× + q f(-1): -1p + q = -5 f(4) : 4p + q = 5 ___________________ - -5p = -10 p = -10/-5 = 2 f(x) = Px + q = 2(4) + q = 5 = 8 + q = 5 q = 5-8 q = -3 f(×) = Px + q f(-6) = 2 (-6) + -3 = -12 + -3 = - 15